Appetites and aspirations: Consuming wildlife in Laos - Singh, Sarinda (The Australian journal of anthropology, 2010)
Research on wildlife use is strongly associated with conservation and environmental debates. Yet, popular beliefs about wildlife consumption also offer many opportunities for discussing identity and social change. To demonstrate this, I examine ideas about eating common types of wildlife in Laos in light of the dialectical contrast between civilised settlements (muang) and the wild forest (pa). The exclusion of wildlife from the widely practised baci ritual and the popularity of wildlife consumption indicate the potency of these animals as social objects. In a contemporary context of widespread social and environmental change across Laos, the practice of eating wildlife is being constructed as an assertion of Lao identity that blends an idealised tradition with a status-conscious modernity. Ambivalent desires for social transformation draw upon ambiguous symbols to find expression in beliefs as well as in popular social practice.